Follicular fluid cerebellin and betatrophin regulate the metabolic functions of growing follicles in polycystic ovary syndrome - Ersahin, Aynur Adeviye; Acet, Mustafa; Ersahin, Suat Suphan; Acet, Tuba; Yardim, Meltem; Kenanoglu, Omer; Aydin, Suleyman (Korean Soc Reproductive Medicine, 2017)
Objective: The aim of this study was to assess the changes of follicular fluid (FF) and serum levels of cerebellin precursor protein 1 (cbln1) and betatrophin in patients with polycystic ovary syndrome (PCOS) undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) with a gonadotropin-releasing hormone (GnRH) antagonist protocol. Methods: Twenty infertile women with PCOS and 20 control women diagnosed as poor responders undergoing ovarian stimulation with a GnRH antagonist were included. Blood samples were obtained during ovum pick-up. Follicular fluid from a dominant follicle was collected from the subjects. Using enzyme-linked immunosorbent assays, FF and serum levels of cblnl and betatrophin were measured in both groups of participants. Metabolic and hormonal parameters were also determined and correlated with each other. Results: Both groups of women had similar serum and FF betatrophin levels (55.0 +/- 8.9 ng/mL vs. 53.1 +/- 10.3 ng/mL, p = 0.11). The serum and FF betatrophin levels of poor responders were found to be similar (49.9 +/- 5.9 ng/mL vs. 48.9 +/- 10.7 ng/mL, p = 0.22). Conversely, the FF cbln1 levels of PCOS women were found to be significantly higherthan the serum cbln1 levels (589.1 +/- 147.6 ng/L vs. 531.7 +/- 743 ng/L, p < 0.02).The FF cbln1 levels of control participants without PCOS were significantly higher than their serum cbln1 levels (5993 +/- 211.5 ng/L vs. 5253 +/- 87.0 ng/L, p = 0.01). Positive correlations were detected among body mass index, insulin resistance, serum insulin, total testosterone, and betatrophin levels in the PCOS group. Conclusion: Follicular fluid betatrophin and cbln1 concentrations may playa pivotal role on follicular growth in PCOS subjects undergoing IVF/ICSI with an antagonist protocol.
Keywords: Antagonist protocol; Betatrophin; Cerebellin; Follicular fluid; Intracytoplasmic sperm injection; In vitro fertilization; Polycystic ovary syndrome